The investment implications of creating friendly environment for the Nigerian child (2004)
This study defined and examined early childhood education, child friendly environment and investment. It was pointed out that without good investment in the jeopardy. This is because pre-school education provides the opportunity, not only for training a child academically, but also giving it an alternative motherly care when the mother otherwise enagaged in economic activities. An observation instrument with fifteen indicators was used to gather data from ten schools of the type under consideration in ibadan Metropolis to evaluate whether or not they were child friendly. Data were anlaysed using percentages. The results showed that though there were some minimally acceptable investment in the sub-sector, but the investment still fell short of what it should be. It was, therefore, recommended that creating child friendly enivroment is not the responsibility of only one party, but of all the stakeholders in the sub-sector.